Saprolegniasis on the eggs of the common carp (Cyprinus carpio L.) with the occurrence of micropredators at Al-Wahda fish hatchery, south of Baghdad - Al-Shammari, R. H.; Al-Mukhtar, E. A.; Habib, K. A. (Iraqi Journal of Aquaculture, 2022)
The aim of the present study is to find out if the occurrence of the zooplankton with the incubated eggs of the common carp (Cyprinus carpio L.) could increase the fungal infection causing saprolegniasis in the main fish hatchery in Iraq during the artificial propagation from April to June 2009. Four eggs treatments were used, the highest hatching rate was 85.8 % in treatment no. 2 in which filtered water was used to incubate the eggs and lowest hatching rate was 21 % in the negative control according to the availability of zooplankton and the absence of fungicidal treatment. Crustacea identified were: Bosmonia, Cyclops, Daphnia, Moina, Nauplii and aquatic insects were: Chironomas, Notonicta, Culex.